Investigation of cloud point extraction for the analysis of metallic nanoparticles in a soil matrix. Issue 1 (3rd November 2016) - El Hadri, Hind; Hackley, Vincent A.
Abstract : The characterization of manufactured nanoparticles (MNPs) in environmental samples is necessary to assess their behavior, fate and potential toxicity. Abstract : The characterization of manufactured nanoparticles (MNPs) in environmental samples is necessary to assess their behavior, fate and potential toxicity. Several techniques are available, but the limit of detection (LOD) is often too high for environmentally relevant concentrations. Therefore, pre-concentration of MNPs is an important component in the sample preparation step, in order to apply analytical tools with a LOD higher than the ng kg −1 level. The objective of this study was to explore cloud point extraction (CPE) as a viable method to pre-concentrate gold nanoparticles (AuNPs), as a model MNP, spiked into a soil extract matrix. To that end, different extraction conditions and surface coatings were evaluated in a simple matrix. The CPE method was then applied to soil extract samples spiked with AuNPs. Total gold, determined by inductively coupled plasma mass spectrometry (ICP-MS) following acid digestion, yielded a recovery greater than 90%. The first known application of single particle ICP-MS and asymmetric flow field-flow fractionation to evaluate the preservation of the AuNP physical state following CPE extraction is demonstrated.